Implantable cardioverter defibrillator - powerful weapon in primary and secondary prevention of sudden cardiac death - Kostić Tomislav; Stanojević Dragana; Gudelj Ognjen; Milić Dragan; Putnik Svetozar; Perišić Zoran; Đinčić Boris; Pavlović Milan; Koraćević Goran; Golubović Mlaċan; Mitov Vladimir; Momčilović Stefan; et al. (Vojnosanitetski Pregled)
Bacgraund/Aim. Sudden cardiac death (SCD) is one of the biggest problems of the contemporary medicine. Large studies showed that anti-arrhythmics, including amiodarone, are not effective in prevention of SCD in the patients with cardiac diseases who were on drug treatment. Those patients who received implantable cardioverter defibrillators (ICD) had better survival. The aim of this paper was to determine whether the patients receiving the ICD in the primary and secondary SCD prevention have longer survival than the patients treated exclusively with drug therapy. Methods. We included 1,260 patients with cardiac insufficiency and reduced left ventricular ejection fraction (LVEF < 35%) who were at high risk for malignant ventricular arrhythmias and SCD. Five hundred forty patients received ICD therapy. The cardiac resynchronization therapy – CRT/ICD group (n = 270) comprised the patients with cardiac insufficiency and CRT/ICD pacemaker at an optimal medical therapy. In the control group (n = 450), there were the patients with cardiac insufficiency (NYHA functional class 3–4, LVEF ≤ 35%, QRS duration ≥ 130 ms), at optimum drug therapy. Results. In the ICD group, there was a statistically significant increase in end-systolic volume (ESV) from 92.68 mL to 99.05 mL. In the group of patients with cardiac insufficiency who were on drug therapy, there was a significant decrease in LVEF (33.15% vs. 30.2%; p = 0.017), 6-minute walk distance (6 MWT distance) (216.55 m vs. 203.27 m, p = 0.003). In the same group, there was an increase in the values of ESV (90.19 mL vs. 95.41 mL; p = 0.011). An increase in the mortality rate in the group of patients with drug therapy compared to the CRT/ICD and ICD groups was statistically significant (p < 0.05). Conclusions. An ICD pacemaker implantation significantly reduces mortality compared to medical therapy only. In addition, the patients who have CRT in addition to ICD pacemaker, have a significantly better quality of life and increase in LVEF.